The first year of implementing a new concept of the journal "Mining of Mineral Deposits" of the National Mining University - Lozynskyi, V.; Sai, K.; Vvedenska, T. (Розробка родовищ, 2017)
This article presents the analysis of Ukrainian mining sciences journal – “Mining of Mineral Deposits” (English acronym – MMD). Our paper presents a case study of a journal in the field of mining sciences and describes the first year of implementing a new concept of the journal. The results can serve as a reference in future studies of the jour-nal in a new form. The findings of future research may be an indication as to whether the adopted policy of interna-tionalization of the journal is effective and increases the impact of the Journal in World Science. Special considera-tion is given to website visitors activity and visits frequency statistics. It appears that MMD is improving its position within the group of leading and original Ukrainian mining periodicals.